Performance analysis of selected database management systems - Kowalczyk, Radosław; Smołka, Jakub (Journal of Computer Sciences Institute, 2024)
The article presents the results of performance tests of database management systems. In order to conduct the tests, an application running in Java environment and using an ORM tool such as Hibernate for communication with the database was used. The tests were carried out for test scenarios such as CRUD operations, join queries, aggregate functions, and filter conditions in queries. The DBMSes used for testing were MySQL, PostgreSQL and H2. Performance analysis looked at the execution time of operations, RAM usage and CPU load. Additionally, tests were carried out for different sizes of user groups using the application. PostgreSQL proved to be the best choice for complex operations.